The role of social network usage factors on the public university student performance in Abu Dhabi - Ali Alrashdi, Ahmed Saeed Awadh (2024)
In the era of digital transformation, social networks have not only altered social interactions but have also significantly impacted educational systems. Despite its ubiquitous adoption, understanding the precise factors that influence student performance within the context of social network usage in higher education remains underexplored. This gap is particularly relevant given the rising importance of quality education in the increasingly competitive global landscape. Thus, the impetus for this research emerges from the need to articulate these influential variables, especially within the confines of higher education institutions in the United Arab Emirates (UAE). The primary aim of this study is to identify and assess the factors that influence the utility of social networks and their subsequent impact on student performance. In addition, the research examines the moderating role of service quality within this relationship. Data were collected via questionnaire surveys from students enrolled at Zayed University and Emirates University who actively utilize social networks for academic purposes. A total of 407 valid responses were analyzed using Structural Equation Modeling (SEM) through SmartPLS software. The findings underscore that performance expectancy and effort expectancy significantly and positively influence student performance. Conversely, variables related to social influence and facilitating conditions were found to have an insignificant impact. Moreover, the study establishes that service quality significantly moderates the relationships between performance expectancy, effort expectancy, and student performance. This research offers empirically supported explanations and predictions about online social network use and its impact on student performance at public higher education institutions in Abu Dhabi. The contributions of this study are threefold: For individuals, it elucidates how social network usage can enhance efficiency, knowledge acquisition, and decision-making quality. For educational organizations, the research provides insights into how social network utilization can positively affect institutional performance metrics. Finally, at a national level, the study offers evidence that effective use of social networks can have broad implications, potentially enhancing various facets of social, economic, and cultural life in the UAE.